Kesejahteraan Psikologis pada Ibu sebagai Orang Tua Tunggal di Kota Malang - Amethysa Iganingrat; Nur Eva (Fakultas Psikologi Universitas Negeri Malang, 2020)
The occurrence of mothers as single parents causes a shift in roles. This role shift can cause various problems, especially psychological well-being problems. Whereas psychological well-being in single mothers is very much needed so that single mothers can carry out their roles well. This study aims to determine the dynamics of psychological well-being in single mothers located in Malang City. Psychological well-being is a state of well-being that refers to one's self-actualization. Psychological well-being includes six aspects, namely self-acceptance, positive relationships with others, self-development, environmental mastery, life goals, autonomy. The research method uses qualitative research methods with a phenomenological approach. Data was collected by using interview techniques and referring to the six aspects of psychological well-being. Data analysis was carried out in several stages, namely, collecting data, reducing data, presenting data, and verifying. In order to obtain credible data, the researcher carried out several stages, namely extending the research time, member check, and expert opinion. Of the three single mothers who have been interviewed, there is one mother who is psychologically prosperous and the other two are still not well psychologically well. The dynamics of psychological well-being can be seen from the existence of good emotional management, good interpersonal relationships, as well as making the right decisions that cause aspects of psychological well-being to be fulfilled. Some aspects such as environmental mastery, autonomy, and self-development have not been good due to financial problems and difficulties in educating children.